Durable complete remission following anti-EGFR antibodies in recurrent metastatic colorectal cancer. (January 2019) - Boudrias-Dalle, Etienne; Cloutier, Magali; Harvey, Marjorie; Leblanc, Guy; Besner-Morin, Olivier; Adam, Jean-Philippe
In this case report, we describe a patient who remains in complete remission two years after the discontinuation of anti-EGFR monotherapy as a third-line treatment, accompanied by persistent severe hypomagnesemia. A 45-year-old Caucasian woman with mCRC started chemotherapy with weekly cetuximab. After ten months of treatment, the therapy was stopped because the patient had persistent grade III hypomagnesemia despite amiloride, oral, and intravenous magnesium. A month later, the patient was switched to panitumumab 6 mg/kg every two weeks for four additional months to avoid weekly visits to the clinic. Following discontinuation of panitumumab, PET scans remain negative to this day, two years after anti-EGFR therapy discontinuation. No factor has been identified to explain the complete and sustained response experienced by this patient. Hypomagnesemia is a common adverse effect of anti-EGFR therapy that can lead to treatment interruption and discontinuation if severe. This case highlights the importance of pursuing anti-EGFR therapy when a response is observed in spite of severe hypomagnesemia. It also provides preliminar y information that anti-EGFR therapy could be stopped after a complete response is obtained.